Instability of an intersecting fault-dyke system during deep rock excavation. (May 2022) - Huang, Xiao; Xu, Nuwen; Wu, Wei; Xiao, Peiwei; Dong, Linlu; Li, Biao
Abstract: Intersecting discontinuities are often encountered in rock engineering and sometimes associated with damaging geohazards. Our understanding of intersecting discontinuities instability remains vastly insufficient due to difficulties in comprehensively monitoring the failure process. Here we use microseismic (MS) monitoring to virtualize the MS events in the rock masses surrounding a powerhouse crown and investigate the effect of geological features on the occurrence of MS events. We subsequently build a three-dimensional numerical model and validate this model using the in-situ measurements by multipoint displacement meters. The numerical results demonstrate how the displacements of surrounding rock masses near the fault and the dyke increase and reveal possible causes, such as stress condition as well as geometry and orientation of rock discontinuities. We also discuss the correlation between the tempo-spatial distribution of MS events and the failure pattern of rock masses and confirm the weakened dyke as the main cause of the rock collapse. This study highlights that the stability of intersecting discontinuities can be controlled by both the geometrical and mechanical properties of individual discontinuities, and attentions should be paid to key properties favorable for rock instability.